HISTORY OF THE STUDY OF ROCK PAINTINGS OF THE NURATA MOUNTAIN RANGE - A.N.Xolmatov; R.Karimov; F.Sh. Kochkarov (Galaxy International Interdisciplinary Research Journal, 2022)
The role and role of historical cultural monuments in the large-scale and full-fledged study of the history of Uzbekistan can not be overemphasized. Monuments of rock paintings, one of such cultural monuments, are stone chronicles that provide valuable information about the spiritual livelihood, art, religion, economic activities, daily lifestyle, social system, as well as ethnographic problems of the inhabitants of various stages of the development of personality history with the essence of their content.